DBU catalyzed metal free synthesis of fused 1, 2, 3-triazoles through [3+2] cycloaddition of aryl azides with activated cyclic C–H acids. Issue 29 (20th July 2016) - Singh, Harjinder; Khanna, Garima; Khurana, Jitender M.
Graphical abstract: Highlights: DBU catalyzed synthesis of fused triazoles. High yield of products and short reaction time. Recyclability of both reaction medium and catalyst. Abstract: DBU catalyzed synthesis of fused 1, 2, 3-triazoles by [3+2] cycloaddition of aryl azides with activated cyclic C–H acids such as dimedone, cyclohexane-1, 3-dione, 5-methylcyclohexane-1, 3-dione, and 2-hydroxynaphthalene-1, 4-dione in PEG-400 has been reported under heating. The important features of this reaction are high yield products, short reaction times, easy availability of starting materials, and recyclability of both reaction medium and catalyst.